Plato's introduction of forms - Dancy, R M (Cambridge University, 2013)
Scholars of Plato are divided between those who emphasize the literature of the dialogues and those who emphasize the argument of the dialogues, and between those who see a development in the thought of the dialogues and those who do not. In this important book, Russell Dancy focuses on the arguments and defends a developmental picture. He explains the Theory of Forms of the Phaedo and Symposium as an outgrowth of the quest for definitions canvassed in the Socratic dialogues, by constructing a Theory of Definition for the Socratic dialogues based on the refutations of definitions in those dialogues, and showing how that theory is mirrored in the Theory of Forms. His discussion ranges in detail over a number of Plato's early and middle dialogues, and will be of interest to readers in Plato studies and in ancient philosophy more generally.